PENERAPAN MEDIA POP-UP BOOK DIGITAL UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA MATERI IPAS SISWA DI SD MUHAMMADIYAH 1 SAMBENG - Nita Dwi Yanti; A.F. Suryaning Ati MZ; Arfian Mudayan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking is one of the essential competencies that should be developed in elementary school Science and Social Studies (IPAS) learning. However, classroom instruction is still predominantly teacher-centered, resulting in limited student engagement and low critical thinking ability. This study aimed to improve students' critical thinking skills through the implementation of a Digital Pop-Up Book on the topic of Energy Transformation for fifth-grade students at SD Muhammadiyah 1 Sambeng. This research employed Classroom Action Research based on the Kemmis and McTaggart model, consisting of two cycles: planning, action, observation, and reflection. The participants were nine fifth-grade students. Data were collected through observation, tests, and documentation and analyzed using descriptive quantitative and qualitative techniques. The findings revealed that the implementation of the Digital Pop-Up Book improved both the learning process and students' critical thinking skills. Teacher activity increased from 76.14% in Cycle I to 95.45% in Cycle II, while student activity increased from 75.00% to 93.18%. Students' average critical thinking score improved from 73.33 to 88.89, and classical learning mastery increased from 66.67% to 100%. These findings indicate that the Digital Pop-Up Book is an effective instructional medium for improving elementary school students' critical thinking skills by promoting active, interactive, and student-centered learning.